Analysis of radiosensitivity in South African cervical and breast cancer patients - Herd, Olivia Jayne (My University, 2015)
Introduction: Ionising radiation can cause DNA double strand breaks (DSB), that result in chromosomal aberrations if un- or mis-repaired. Individuals with compromised DNA damage repair mechanisms display increased chromosomal radiosensitivity. The G0-micronucleus assay (MN assay) and the γ-H2AX assay are two assays used in radiobiology to study DNA DSB and repair. Breast cancer is the leading cancer amongst South African women, with a lifetime risk of 1 in 34. Since most cancer patients in South Africa present with late-stage disease, chemotherapy and radiotherapy are commonly-used treatments. Several international studies have shown breast cancer patients to be more chromosomally radiosensitive than healthy controls. These studies have not been confirmed on a cancer population living in South Africa. Cervical cancer is the second most common cancer in South Africa; however, it is the leading cancer amongst black women with a lifetime risk of 1/35 compared to 1/82 in white women. Studies show a genetic link to cervical cancer susceptibility and DNA damage repair genes. International studies on radiation-induced DNA damage in lymphocytes of cervical cancer patients remain inconclusive and have never been performed on a South African population. Cervical cancer is caused by infection with the Human Papilloma Virus (HPV). Human Immunodeficiency Virus (HIV), HPV and cervical cancer are epidemiologically linked. Due to the high rate of HIV in South Africa, a significant proportion of cervical cancer patients receiving radiotherapy treatment will be HIV-positive. Studies show an effect of HIV on chromosomal radiosensitivity, however this has not been confirmed on a cancer population. The MN assay on the biopsies and exfoliated cervical cells of cervical cancer
Keywords: Breast Neoplasms -- radiography; Cervix Neoplasms -- radiography